Model Kegiatan Seni Tari Untuk Membentuk Akhlak Peserta Didik Di SD - Yuliana Indriyaningsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: In this study, researchers found the attitudes and behaviors that are not good, researchers discovered this phenomenon in SD N jatisawit 01 Sub Brits . In this 01 SD N jatisawit researchers looked at the low value of mutual respect and the respect shown learners , low learners concern for the environment , and the lack of a good ethical attitude indicated learners in school life . Based on the problems that are found , researchers conducted a study that tried to find the model of dance tradidional extracurricular activities that can form the character of students of SD N Jatisawit 01 Brits. This study aims to determine how the model extracurricular dance traditionally done in SD N Jatisawit 01 Brits and want to know whether the model of traditional dance extracurricular activities undertaken to establish the character of students of SD N Jatisawit 01 Brits . This study is an experimental study that uses qualitative - descriptive approach to analyzing research data based methods Research & Development (R&D). Keywords : extracurricular, traditional dance, characters, learners.